Scope and Limitations of Reductive Amination Catalyzed by Half-Sandwich Iridium Complexes Under Mild Reaction Conditions - Nguyen, Dat P. (Tetrahedron Lett, 2020)
The conversion of aldehydes and ketones to 1° amines could be promoted by half-sandwich iridium complexes using ammonium formate as both the nitrogen and hydride source. To optimize this method for green chemical synthesis, we tested various carbonyl substrates in common polar solvents at physiological temperature (37 °C) and ambient pressure. We found that in methanol, excellent selectivity for the amine over alcohol/amide products could be achieved for a broad assortment of carbonyl-containing compounds. In aqueous media, selective reduction of carbonyls to 1° amines was achieved in the absence of acids. Unfortunately, at Ir catalyst concentrations of <1 mM in water, reductive amination efficiency dropped significantly, which suggest that this catalytic methodology might be not suitable for aqueous applications where very low catalyst concentration is required (e.g., inside living cells).